Implications Of Economic Sanctions On Potential Crude Oil And Natural Gas Prices For Russia Violations - Miskha Alemina; Rachma Indriyani; Ayub Torry Satriyo Kusumo (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
International sanctions are still an important diplomatic instrument used by international organizations such as the United Nations (UN) or a group of countries to target sanctions. One of the existing international sanctions is economic sanctions, which have already been applied to Russia. Economic sanctions against Russia as a consequence of the illegal annexation of Crimea and for under mining territorial integrity of Ukraine. It is believed that the imposition of economic sanctions against Russia will trigger an escalation of the price of crude oil and natural gas on the global market because Russia is ranked as the largest supplier of crude oil and natural gas in the world. The research method used is normative juridical with comparative approach by comparing how economic sanctions have an impact on the Russian economy before and after they are implemented. We argued that the inflation is becoming scarce on the global market while for Russia this case causes increase inflation due to Russia losing most of its shares in international markets.